Effect of nano and micro SiO2 on brittleness and fracture parameters of self-compacting lightweight concrete. (13th September 2021) - Afzali-Naniz, Oveys; Mazloom, Moosa; Karamloo, Mohammad
Highlights: The fracture behavior of SCLC with micro and nano silica was assessed. Bazant's type II size effect law was used to model the size effect. Fracture toughness and energy and crack-tip opening displacement were calculated. Variation of fracture energy versus concrete compressive strength was considered. Abstract: In the present study, 16 mix compositions with two different water to binder ratios of 0.35 and 0.45 were designed to assess the fracture behavior of self-compacting lightweight concrete (SCLC) mixes with micro and colloidal nano silica. To do so, 192 notched beam specimens of various sizes were cast. The contribution of 10% micro silica (MS), 1%, 3%, and 5% colloidal nano silica (CNS) were considered in forms of binary and ternary mixtures and then the results were compared with those of controlling specimens. In order to analyze the fracture behavior of mixes, type-II size effect law were used and all tests were conducted in accordance with RILEM recommendations. The results indicated that W/B ratio as well as the replacement of MS and CNS with cement could substantially affect the fracture behavior of SCLC mixes. For instance, the use of 10% MS in the absence of CNS has led to the increase of fracture energy by 9.8% and 16.4% for mixes with W/B ratios of 0.35 and 0.45, respectively, while at the same level of 10% MS replacement by cement, the replacement of 1%, 3%, and 5% CNS by cement, has improved the initial fracture energy of the W35 group of mixes by 11.38%, 16.58%, and 8%, respectively. This was 1.8%, 10.6%, and 4.6% for W45 group of mixes with 10% of MS. In addition, this research showed that the proposed model could conveniently predict the experimental results.